Attitudes and beliefs about hand hygiene among paediatric residents: a qualitative study. Issue 6 (14th December 2012) - Dixit, Devika; Hagtvedt, Reidar; Reay, Trish; Ballermann, Mark; Forgie, Sarah
Abstract : Background: Despite the knowledge that contaminated hands play an important role in the transmission of healthcare-associated pathogens, and that hand hygiene (HH) reduces the transmission of these organisms, healthcare worker's adherence with HH is poor. Objective: To understand the common beliefs and attitudes held by paediatric residents about HH. Design: Qualitative study design. Setting: Tertiary care paediatric hospital in Edmonton, Canada. Methods: Semistructured interviews were conducted and themes were identified from interviews. Participants: 22 paediatric residents. Results: Paediatric residents self-reported their HH adherence at 70–99% and perceived hospital-wide adherence at 45–80%. Four major themes were identified during interviews including the importance of role modelling, balancing time spent on HH with other competing factors, self-protection as a driving factor for HH and cues as an important part of habit that stimulate HH. Conclusions: Staff physicians were viewed as integral to initiating group HH events, but at times, the first person in the room acted as a role model for the rest of the group. In certain instances, such as a cardiac arrest, decreased adherence with HH was viewed as acceptable. Residents engaged in HH to protect their own health. Residents relied on personal cues, which they integrated into their own HH habit. Future HH adherence strategies should ensure that the physician training environments permit the formation of good attitudes and habits towards HH. There are no additional data available.